Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1080/15332640.2020.1845901
|View full text |Cite
|
Sign up to set email alerts
|

Drinking motives, cultural orientations, and alcohol use among Hispanic college students at the U.S.–Mexico border

Abstract: This postprint may not exactly replicate the final, proof-edited version of the article.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 54 publications
(75 reference statements)
2
7
0
Order By: Relevance
“…Moreover, negative drinking consequences are especially prevalent among Hispanic college students living on the US-Mexico border (Lui et al, 2022). Overall, Hispanic college students are at an increased risk of excessive alcohol use, which has the potential to increase the risk for alcohol-related problems.…”
Section: Alcohol Use and Alcohol Problems Among Hispanic College Stud...mentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, negative drinking consequences are especially prevalent among Hispanic college students living on the US-Mexico border (Lui et al, 2022). Overall, Hispanic college students are at an increased risk of excessive alcohol use, which has the potential to increase the risk for alcohol-related problems.…”
Section: Alcohol Use and Alcohol Problems Among Hispanic College Stud...mentioning
confidence: 99%
“…Previous research has also found that there is a higher level of binge drinking among Hispanic college students compared to non‐Hispanic college peers. Specifically, on average, 50% of Hispanic college students report binge drinking at least once a week (Lui et al., 2020; McCabe et al., 2019; Venegas et al., 2012; Zamboanga et al., 2006). Furthermore, research indicates that Hispanics who do develop alcohol use disorders will have significantly higher reoccurring and persistent alcohol‐related problems as opposed to their non‐Hispanic White counterparts (Chartier & Caetano, 2010).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among high school seniors, Hispanic individuals were more likely to report feeling the need to reduce or stop alcohol use, despite lower levels of alcohol consumption than their White peers (Terry-McElrath & Patrick, 2020). In the context of coping motives-a set of reasons that is most closely linked to harmful alcohol use-and social and enhancement motives-the most common reasons for alcohol use among college students ETHNIC DIFFERENCES IN DRINKING REFUSAL EFFICACY & ALCOHOL USE 5 (Lui et al, 2020b;Madson et al, 2015;Martens et al, 2008;Read et al, 2003), greater resilience can reduce alcohol consumption and negative drinking-related consequences (Sanchez et al, 2022). These findings suggest that being resilient and able to resist drinking in high-risk situations may be an important protective factor for alcohol-related problems.…”
Section: Hispanic Alcohol Use and Ethnic/racial Disparitiesmentioning
confidence: 99%
“…Being more collectivistic may be linked to lower tendencies to turn down drinks or resist the temptation to engage in alcohol consumption-especially in social contexts. A recent study indicated that drinking to conform to social norms was positively associated with alcohol-related problems among Hispanic college students at the US-Mexico border (Lui et al, 2020b). Overarching social factors are not as susceptible to intervention, whereas drinking refusal self-efficacy is malleable to change.…”
Section: Hispanic Alcohol Use and Ethnic/racial Disparitiesmentioning
confidence: 99%